THE LMC SUPPORT INITIATIVE -- BUILDING SUPPORT FROM TOBACCO INDUSTRY SUPPLIER UNIONS (Tufts Archival Research Center, 2007)
Marginalia; Report outlining the Labor Management Committee (LMC) Support Initiative. Acknowledges 'difficult' legislative and administrative climate surrounding the tobacco industry. Seeks to gain support by allying with industry supplier unions.